Meaning in motion : new cultural studies of dance - Desmond, Jane (Post-contemporary interventions., 1997)
"Dance, whether considered as an art form or embodied social practice, as product or process, is a prime subject for culturalal analysis. Yet only recently have studies of dance become concerned with the ideological, theoretical, and social meanings of dance practices, performances, and institutions. In Meaning in Motion, Jane C. Desmond brings together the work of critics who have ventured into the boundaries between dance and cultural studies, and thus maps a little-known and rarely explored critical site." "Writing from a broad range of perspectives, contributors from disciplines as varied as art history and anthropology, dance history and political science, philosophy and women's studies chart the questions and challenges that mark this site. How does dance enact or rework social categories of identity? How do meanings change as dance styles cross borders of race, nationality, or class?. How do we talk about materiality and motion, sensation and expressivity, kinesthetics and ideology? The authors engage these issues in a variety of contexts: from popular social dances to experimentation of the avant-garde; from nineteenth-century ballet and contemporary Afro-Brazilian Carnival dance to hip hop, the dance hall, and film; from the nationalist politics of folk dances to the feminist philosophies of modern dance. Giving definition to a new field of study, Meaning in Motion broadens the scope of dance analysis and extends to cultural studies new ways of approaching matters of embodiment, identity, and representation."--Jacket